Application of the Problem-Based Learning Model to Improve Grade 8 Students' Critical Thinking Skills on Respiratory System Material - Afreni Hamidah; Evita Anggereini; Vera Yulanda (Yayasan Keluarga Guru Mandiri, 2025)
Biology is part of the natural sciences, which include laws and principles resulting from scientific processes that require problem-solving through critical thinking skills. However, critical thinking in biology learning is still relatively low. Training students' critical thinking skills can be enhanced by combining the use of models, media, strategies, and learning approaches that stimulate their critical thinking abilities. This research aims to determine the effect of implementing problem-based learning with E-LKPD as an effort to improve the critical thinking skills of Grade 8 SMP students in relation to the respiratory system. This research is considered quasi-experimental, utilizing a non-equivalent control group design. The sampling technique for the essay is purposive sampling. Critical thinking skills are evaluated through standardized tests. The data analysis technique employed the independent sample T-test. The effectiveness of the PBL model, after being implemented, shows that students' critical thinking skills have increased, as evidenced by a Cohen's d value of 1.0. These results were then interpreted to show that the problem-based model with E-LKPD influenced critical thinking skills, ranking in the high category with a percentage of 84%. The conclusion is that the Problem-based Learning model can be used to improve students' critical thinking skills in science learning, especially in the context of the respiratory system.